Re-Visioning Public Health Approaches for Protecting Children - Lonne, Bob.; Scott, Deb.; Higgins, Daryl; Herrenkohl, Todd I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume provides readers around the globe with a focused and comprehensive examination of how to prevent and respond to child maltreatment using evidence-informed public health approaches and programs that meet the needs of vulnerable children, and struggling families and communities. It outlines the system failures of contemporary forensically-driven child protection practice. Detailed guidance is provided about how to re-think earlier intervention strategies, and establish stronger and more effective programs and services that prevent maltreatment at the population level. Service user and stakeholder perspectives, particularly from marginalized groups including Indigenous peoples, highlight how public health approaches can better support families and keep children safe. Case studies from different countries grapple with the fraught nature of large system change and the various strategies needed to effect multi-level reforms. Presenting the reader with an array of innovative services used in different institutional and community context, this volume confronts the complex challenges found in implementing successful prevention programs that are aligned with diverse cultural and political environments and community expectations.
Part I: The Policy and Program History of Child Protection -- Chapter 1. The Successes and Limitations of Contemporary Approaches to Child Protection (Daryl Higgins, Bob Lonne, Debbie Scott, and Todd Herrenkohl) -- Chapter 2. Stakeholder's Experiences of the Forensic Child Protection Paradigm (Helen Buckley, Morag McArthur, Tim Moore, Erica Russ, and Tania Withington) -- Chapter 3. Assessing the Outcomes of Alternative Care and Treatment Responses (Amy Conley Wright and Melissa Kaltner) -- Chapter 4 'Everybody's Responsibility': Exploring the Challenges of Community Engagement in Child Neglect (Nigel Parton and Sasha Williams) -- Part II: Conceptualising Public Health Approaches -- Chapter 5. Changing and Competing Conceptions of Risk and their Implications for Public Health Approaches to Child Protection (Nigel Parton) -- Chapter 6. Using an Injury Prevention Model to Inform a Public Health Approach to Child Protection (Carol W. Runyan and Desmond K. Runyan) -- Chapter 7. Intersecting Forms of Child Victimization and Public Health Prevention (Todd I. Herrenkohl and J. Bart Klika) -- Chapter 8. How Universal Services Provide the Foundation for Effective Public Health Universal Services: The Foundation for Effective Prevention (Deborah Daro and Cara Karter) -- Chapter 9. Families - Private and Sacred: How to Raise the Curtain and Implement Family Support from a Public Health Perspective (Daryl Higgins, Matt Sanders, Bob Lonne and Dominic Richardson) -- Chapter 10. Child Sexual Abuse Prevention Strategies for Population-Level Change: Challenges and Future Directions (Antonia Quadara) -- Chapter 11. Youth-Serving Organization Safety Risks and the Situational Prevention Approach (Keith Kaufman, Marcus Erooga, Daryl Higgins and Judith Zatkin) -- Chapter 12. How Can Differential Response Inform a Public Health Approach to Child Maltreatment Prevention? (Lisa Merkel-Holguin, Tamara Fuller, Marc Winokur, Ida Drury and Bob Lonne) -- Chapter 13. Bringing a Health Equity Perspective to the Prevention of Child Abuse and Neglect (Joanne Klevens and Marilyn Metzler) -- Chapter 14. Critiques of a Public Health Model in Child Maltreatment (Mel Gray and Leanne Schubert) -- Part III: Addressing Operational and Systemic Issues -- Chapter 15. What are the Risks and Obstacles in Implementing a Public Health Approach to the Well-Being and Protection of Children? (Maria Harries and Melissa O'Donnell) -- Chapter 16. The Role, Importance and Challenges of Data for a Public Health Model (Debbie Scott and Agatha Faulkner) -- Chapter 17. Understanding the Neighbourhood and Community Factors Associated with Child Maltreatment (Paul Bywaters) -- Chapter 18. Framing Child Protection as a Public Health Law Issue (Donald C. Bross and Ben Mathews) -- Chapter 19. Innovative Approaches to Improving Outcomes for Children Involved with Child Welfare: Youth Mentoring (Heather Taussig and Lindsey Weiler) -- Chapter 20. Understanding Trauma and Child Maltreatment Experienced in Indigenous Communities (Deb Duthie, Sharon Steinhauer, Catherine Twinn, Vincent Steinhauer and Bob Lonne) -- Chapter 21. Problems in Understanding Program Efficacy in Child Welfare (Melissa Jonson-Reid and Chien-jen Chiang) -- Chapter 22. Re-visioning Education and Training for Child Protection using a Public Health Approach (Kerryann Walsh) -- Chapter 23. A Good Fit? Ireland's Programme for Prevention, Partnership and Family Support as a Public Health Approach to Child Protection (John Canavan, Carmel Devaney, Caroline McGregor and Aileen Shaw) -- Chapter 24. Collaborative Service Delivery: Catalyst to Innovation in Policy and Practice in Alberta, Canada (Rhonda Barraclough, Kim Spicer, Joni Brodziak, Kassidy Green and Bruce MacLaurin) -- Chapter 25. Building Research Capacity in Child Welfare in Canada: Advantages and Challenges in Working with Administrative Data (Nico Trocmé, Tonino Esposito, Barbara Fallon, Martin Chabot and Ashleigh Delaye) -- Chapter 26. Combining Public Health Approaches with IncreasedFocus on Risk and Safety: A Norwegian Experience (Bente Heggem Kojan, Edgar Marthinsen and Graham Clifford) -- Part IV: Trends and Future Directions -- Chapter 27. Child Maltreatment as Social Harm (Nigel Parton) -- Chapter 28. New Directions for Public Health Approaches: Key Themes and Issues (Todd Herrenkohl, Bob Lonne, Deb Scott and Daryl Higgins).
Keywords: Education; Children; Public health; Family policy; Social service; Childhood Education; Public Health; Children, Youth and Family Policy; Social Work